PERKEMBANGAN LARVA DALAM EMBRIOGENESIS KARANG Acropora HASIL PEMIJAHAN EX-SITU - Yusuf, Syafyudin; Zamani, N P.; Jompa, J. (Torani Journal of Fisheries and Marine Science, 2014)
Fertilization and larval development determine the coral population survivalof species, which has adifference characteristic of embryogenesis. This research wasaimed to compare the embryo and larvaldevelopment spawned in November 2011 in Grear Barrier Reef, Australia.Embryonic cellsdevelopment wereobserved in interval timesfrom one cell of egg tomulticellular stage (prawnchip), and larval developmentobserved from the prawnchip stageto the planulae.The results showed the development of embryos and larvaesignificantly differed between two species, i.e. embryos and larvae of Acropora millepora grew faster thanA.tenuis. The maximum size of planulae larvae of A. millepora (800-1000 μm) is biggerthan A. tenuis (650-900μm). Embryo and larvae development were different due to species variability, hence this reseach can beadapted for laboratory proccess of coral larvae nursery. Keywords: embryo, planulae, Acropora millepora, A. Tenuis